Las pensiones alimenticias destinadas a las juntas cantonales vulneran los derechos de los niños, niñas y adolescentes y adultos mayores, de acuerdo al art. 304 numeral 4 del Código de la Niñez y Adolescencia.” - Castro Quizhpe, Ivelisse Yesenia (2015)
Article 35 of the Constitution of the Republic of Ecuador, among others to protect children and adolescents as priority groups will receive priority attention and specialized in public and private spheres. One way of financing Cantonal Council for Children and Adolescents is as stated in Article 304 paragraph 4 of the Code of Childhood and Adolescence expressing "Municipal funds, within their powers, I have as a resource 4. 100% of maintenance is not used for more than six months in his constituency" But it happens that is maintenance awarded to food people, for the right to food of children, adolescents and adults and adults considered as holders of rights under this Act, which spend some time and could not be charged no is legal to pass Cantonal Council for Children and Adolescents, because they are acquired rights of these people, what to look for are the appropriate means for people to cash their pension assigned to them. It happens that maintenance payments deposited in Judicial Units of Childhood and Adolescence, but then spend the charge Cantonal Boards, which is contrary to what is stated in Article 44 of the Constitution of the Republic of Ecuador the state, society and family a priority to promote the integral development of children and adolescents, and ensure the full exercise of their rights; will be addressed at the beginning of their interests and their rights will prevail over those of others. The Article 298 of the Code on Children and Adolescents provides that the budget of the National Council for Children and Adolescents will be financed by the national budget of the State, other public and private sources, and those generated by self. It is the obligation of the State to provide financial resources for the operation of the National Council for Childhood and Adolescence. In each municipality the Cantonal Advice Children and Adolescents are created, being a collegiate body cantonal level, composed of equal numbers of representatives of the State and civil society, to develop local policies and propose to the City Council. In each municipality has an obligation to provide the financial resources necessary for the efficient operation of the District Council for Children and Adolescents and the Cantonal Board of Protection of Children and Adolescents, their jurisdiction. If maintenance payments are allocated to the Cantonal Boards of Childhood and Adolescence, violates the rights enshrined in Article 45, Section Two of the Constitution of the Republic of Ecuador and others that children and adolescents have the right to the integrity physical and mental; to comprehensive health and nutrition; education and culture, sport and recreation; social security; to have a family and enjoy family and community life; social participation; to safeguard their freedom and dignity; to be consulted on matters that affect them; to educate a priority in their own language and cultural contexts of their peoples and nationalities; and receive information about their parents or absent, except family members would be detrimental to their welfare